2022
DOI: 10.1080/15592294.2022.2090654
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid-related anti-inflammatory effects in force-stressed PdL fibroblasts are mediated by H3 lysine acetylation associated with altered IL10 expression

Abstract: The initiation of a spatially and temporally limited inflammation is essential for tissue and bone remodelling by the periodontal ligament (PdL) located between teeth and alveolar bone. Nutritional components may cause alterations in the inflammatory response of PdL fibroblasts to mechanical stress such as those occurring during orthodontic tooth movement (OTM). Recently, we reported an attenuated pro-inflammatory response of human PdL fibroblasts (HPdLFs) to compressive forces when stimulated with oleic acid … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Acetylation and deacetylation are essential chemical modifications of histones, which are associated with gene expression or gene silencing [ 42 ]. It has been demonstrated that histone 3 acetylation (H3ac) is associated with IL-10 expression in force-stressed PDL fibroblasts [ 43 ]. Our research verified that H3ac is significantly elevated by compression force.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylation and deacetylation are essential chemical modifications of histones, which are associated with gene expression or gene silencing [ 42 ]. It has been demonstrated that histone 3 acetylation (H3ac) is associated with IL-10 expression in force-stressed PDL fibroblasts [ 43 ]. Our research verified that H3ac is significantly elevated by compression force.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescent staining was performed as previously described [49][50][51]. Briefly, following 10 min fixation with paraformaldehyde (PFA, 4%), three washing steps in 1× PBS/0.1% Triton X (Triton X ® 100, Carl Roth GmbH + Co. KG, Karlsruhe, Germany) were applied.…”
Section: Immunofluorescent Stainingmentioning
confidence: 99%
“…To visualize the cytokine secretion of the stimulated hPdLFs, activation of the monocytic THP1 cells was performed like previously described [16,49,50,52]. Briefly, Celltracker CMFDA (15 µM, 30 min, Thermo Fisher Scientific, Carlsbad, CA, USA)-stained nonadherent THP1 cells were applied for 30 min to the hPdLFs cultured on the coverslips.…”
Section: Thp1 Activation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty acids could serve as an alternative source of acetyl-CoA, thereby affecting epigenetic histone marks, such as histone 3 lysine acetylation. Recently, Schuldt et al demonstrated that OA-related anti-inflammatory effects in fibroblasts are mediated by histone 3 lysine acetylation associated with increased expressions of anti-inflammatory cytokines [ 114 ]. These results suggest that OA effects could be exerted by different mechanism by histone acetyltranferase activation and SIRT-1-independence [ 115 ].…”
Section: Oleic Acid and Epigeneticsmentioning
confidence: 99%